In-Class EMI Challenges Arising in an Arabian Gulf Engineering Programme - Holi Ibrahim Holi (SAGE Open)
This paper draws on the researcher’s PhD research and thesis, which investigated Omani engineering students’ in-class learning-related barriers in an Omani English-medium engineering programme. An interpretive qualitative design was used to examine students’ EMI in-class-related challenges and difficulties. Semi-structured interviews were utilized to collect the main data of the study. Twelve engineering students, eight engineering teachers and five EAP instructors. Subsequent classroom observations of four EAP and four engineering workshops yielded field notes to provide further context. Data were analysed thematically. Findings pointed to salient classroom-related problems in EMI varied in their nature; some related to reading, writing and speaking skills, as well as spontaneous classroom discussions and oral tasks. These challenges varied from one specific engineering discipline to another due to the conceptual and epistemological differences between them. Additionally, the study identified the most significant obstacles including insufficient previous learning, the inadequacy of pre-sessional and in-sessional course resources, limited interaction between EAP instructors and subject tutors, and inadequate teacher development opportunities in EMI offered to subject tutors. The original study showed that various measures can be taken to improve EMI. Whilst findings resonate with other studies of EMI classrooms across the globe, this study provides a unique contribution by considering specific case of Omani engineering programmes. Conclusions were drawn and recommendations are now made for EMI policy, teacher collaboration and teacher development.